Methods of Control of Explosion Energy Distribution in Rocks (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
model of the action of an explosion on a medium discussed in Section 3 makes it possible to judge the quality of crushing only by the final results and does not allow one to study the processes occurring in the medium over time, since from the accepted assumptions about the incompressibility and instantaneous transfer of charge energy in the medium it follows that the energy spreads instantly.